Clinical Features and Outcomes of Dengue Encephalitis: Analysis of five deaths in the 2023-2024 Epidemic, Paraguay - Ramírez, Alcide Florenciano; Pérez Velilla, María Adela; Garlisi Torales, Luciana Daniela (International Journal of Neurology, 2025)
Introduction: Dengue encephalitis is a rare but severe neurological complication of dengue fever, the incidence of which increases during epidemics. This disorder results from direct invasion of the virus into the central nervous system or from an exacerbated inflammatory response. Objective: To describe and analyze clinical cases of 5 patients who died from dengue fever during the 2023-2024 epidemic. Clinical case: The analysis included the 5 confirmed clinical cases of dengue encephalitis that resulted in death. The patients’ ages ranged from 10 to 97 years, with a predominance of women (n = 3). The findings are presented according to the research objectives, with emphasis on common patterns observed before the fatal outcome. Discussion: During the dengue outbreak in Paraguay (2023–2024), five fatal cases of encephalitis were reported, all with severe neurological symptoms such as seizures and coma. Most presented with high viral load and elevated levels of proinflammatory cytokines, associated with cerebral edema and multiorgan failure. The DENV-2 serotype predominated in patients with comorbidities. Neurological manifestations appeared early, without the need for thrombocytopenia. These findings reflect an intense inflammatory response and underscore the importance of timely diagnosis and treatment. Conclusions: The five patients who died from dengue were successfully described. The implementation of active surveillance strategies and specific protocols could improve early detection and reduce associated mortality.